Tourists’ Perceived Destination Competitiveness in Protected Areas: The Case of Semenggoh Nature Reserve - Jun Zhou, Thong; May Chiun, Lo; Mohamad Kadim, Suaidi; Abang Azlan, Mohamad; Chee Hua, Chin (Academic Research Publishing Group, 2019)
Ecotourism is referred to sustainable tourism, whereby responsible travel is endorsed, especially in natural areas that emphasize on relaxation. In Malaysia, the richness of natural areas leads ecotourism to become one of the rapidly growing industries within the nation. Thus, there is a need for complete understanding of ecotourism practice in planning, developing, and resources management to ensure sustainability without causing environmental degradation. Over the decades, people are progressively pursuing for reconnection with the nature for pukka natural experiences during their travel. This study intends to identify the impacts of natural resources, accessibility, cultural uniqueness, carrying capacity, and perceived values on tourism destination competitiveness from tourists’ perspectives. A total of 157 respondents had participated in completing the questionnaire. WarpPLS (version 6.0) was applied to assess the developed model based on path modelling followed by bootstrapping. The results revealed that accessibility and cultural uniqueness are positively and significantly correlated to tourism destination competitiveness based on tourists’ perspectives. Surprisingly, natural resources, carrying capacity, and perceived values were observed to be no significant relationship with tourism destination competitiveness. The implications, limitations, and directions for future research are further discussed.